The Lalaran Method of Ro'sun Sirah Book’s to Increase Arabic Vocabulary Student at Darun Najah Sambikarto Islamic Boarding School | Metode Lalaran Kitab Ro’sun Sirah untuk Meningkatkan Kosakata Santri di Pondok Pesantren Darun Najah Sambikarto - Abdul Wahab; Ulfa Himmatus Sya'adah; Edi Kurniawan Farid (An-nahdloh : Journal of Arabic Teaching, 2023)
Arabic is one of the languages that is considered complicated by students and students in Indonesia, but there is also an institution that applies language learning so that the language is liked by students and students. With the right method and preferred by students and students, Arabic will develop faster, this is because many institutions have less developed Arabic.  With this problem, the Darun Najah Islamic Boarding School has a vision to provide ro'sun sirah lessons to provide new insights for students. This work aims to introduce the textbook of the Salafiyah Islamic boarding school, namely the book of ro'sun sirah. Which at the Darun Najah Sambikarto Islamic boarding school this book became a book studied by students at the ula level. In this book contains Arabic mufrodat-mufrodat in Javanese so that it can help students to increase memorization of mufrodat to increase vocabulary . This work aims to introduce the textbook of the Salafiyah Islamic boarding school, namely the book of ro'sun sirah. Which at the Darun Najah Sambikarto Islamic boarding school this book became a book studied by students at the ula level. This book contains Arabic mufrodat that uses Javanese so that it can help students to increase memorization of mufrodat to increase their Arabic vocabulary. Therefore we strongly believe that by providing teaching through the book of ro'sun sirah provides development and improvement of mufrodat for students. The reasoning method applied in Islamic boarding schools is to read it using tones or songs so as not to make a boredom for students, the implementation time is when the ngaji diniyah schedule begins. We use analytical descriptive qualitative methods in which we observe learning in Pondok Darun Najah Sambikarto. This observation is through a book called Kitab Ro'sun Sirah (Arabic poetry) which contains Arabic mufrodat and its meaning in Javanese. The purpose of this research is to introduce the book of salaf scholars who can help students to memorize Arabic mufrodat easily, the result of the application of the reasoning method for students is the increase in memorization of Arabic mufrodat santri at the elementary level, so that students will more easily recognize Arabic at this early age.